Impact of systemic hypoxemia on cancer aggressiveness and circulating vascular endothelial growth factors A and C in gastroesophaeal cancer patients with chronic respiratory insufficiency - Krzystek-Korpacka, M.; Matusiewicz, M.; Diakowska, D.; Grabowski, K.; Blachut, K.; Kustrzeba-Wojcicka, I.; Gamian, A. (Experimental Oncology, 2007)
Aim: Due to the common etiologic factor, a considerable number of esophagogastric cancer patients suffer from respiratory insufficiency in course of chronic obstructive pulmonary disease, primary to cancer. Systemic hypoxemia may account for poor oxygenation of tumor tissue-a main driving force of tumor neoangiogenesis. We hypothesized that in cancer patients with respiratory insufficiency, systemic hypoxemia may be related to enhanced aggressiveness of cancer on one side and to the elevation of angiogenic factors on the other. Methods: The levels of vascular endothelial growth factors A and C were determined with immunoenzymatic methods in patients diagnosed with esophagogastric cancer with or without co-existing respiratory insufficiency in course of chronic obstructive pulmonary disease and in healthy controls. Blood gasometry and hemoglobin levels of cancer patients were related to cancer histology and TNM status, and to circulating vascular endothelial growth factors A and C. Results: Patients with systemic hypoxemia had higher incidence rates of locally advanced tumors. Partial oxygen pressure and blood oxygen saturation were significantly lowered in patients with T4 cancers as compared to less advanced onces. Circulating vascular endothelial growth factor A, but not C, was more elevated in esophagogastric cancer patients with co-existing respiratory insufficiency, as compared to those without respiratory insufficiency. Vascular endothelial growth factor A was also strongly related to the extension of primary tumor. Conclusion: Our results show that systemic hypoxemia in esophagogastric cancer patients is associated with the extension of primary tumor and that this effect might be mediated by the up-regulation of circulating vascular endothelial growth factor A.